PENGARUH PERSEPSI SISWA PADA PEMBELAJARAN JARAK JAUH TERHADAP HASIL BELAJAR PAI - Sri Riatni; Abdul Khoir; Irham Irham (Turats, 2023)
This study aims to determine the effect of students' perceptions of distance learning on students' PAI learning outcomes in terms of knowledge, attitudes and skills at SMA Widya Nusantara. The research method used is a survey method with a correlational approach. The sample used was 25 students obtained by the Simple Rondom Sampling technique. Collecting data on the variable X using a questionnaire and the variable Y using the documentation of students' PAI learning outcomes. The results showed that there was an effect of students' perceptions of distance learning on students' PAI learning outcomes in terms of knowledge, attitudes, and skills at SMA Widya Nusantara. Aspects of knowledge obtained the value of Sig. 0.000 then the value is 0.000 <0.05 or it can be seen that the t count value is 5.096 then 5.096> 2.069 (t table) then it is stated that H1 is accepted Ho is rejected, and for the relationship of variable X to variable Y on the aspect of knowledge 0.728, by contributing the variance of the X variable to the variable Y on the knowledge aspect 53%. The attitude aspect is obtained by the value of Sig. 0.000 then the value is 0.000 <0.05 or it can be seen that the t count value is 5.656 then 5.656> 2.069 (t table) then it is stated that H1 is accepted Ho is rejected, and for the relationship of variable X to variable Y in the attitude aspect 0.763, by contributing to the variance of the X variable to the variable Y on the attitude aspect 58.2%. Aspects of skills obtained the value of Sig. 0.000 then the value is 0.000 <0.05 or it can be seen that the t count value is 5.403 then 5.403> 2.069 (t table) then it is stated that H1 is accepted Ho is rejected, and for the relationship of variable X to variable Y in the skill aspect 0.748, by contributing the variance of the X variable to the variable Y on the skill aspect 55.9%.